2017
DOI: 10.1111/jora.12367
|View full text |Cite
|
Sign up to set email alerts
|

Tween Television and Peers: Reinforcing Social Agents in Early Adolescents' Body Surveillance and Self‐Objectification

Abstract: Sociocultural models of body image posit that the media and peers play a role in early adolescents' body dissatisfaction. Introducing a sociocultural perspective on youth sexualization, the present three-wave panel study (N = 968, M = 11.30) sought to examine the role of tween television and peer appearance conversations in early adolescents' body surveillance and self-objectification over time. Special attention was given to the mediating role of media internalization in these relationships. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
0
4
0
1
Order By: Relevance
“…Our findings suggest that preventing the development of self-objectification may potentially assist in addressing poor body image among children. Fredrickson and Roberts (1997) suggested that cultural practices of sexual objectification socialize individuals to engage in self-objectification and many social influences, including the mass media, parents, and peers reinforce self-objectification (Fredrickson & Roberts, 1997; Rousseau & Eggermont, 2018; Webb et al, 2017). Development of effective prevention programs requires research to identify which sources of sexual objectification are more likely to result in self-objectification among children and to identify other potential antecedents of self-objectification.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that preventing the development of self-objectification may potentially assist in addressing poor body image among children. Fredrickson and Roberts (1997) suggested that cultural practices of sexual objectification socialize individuals to engage in self-objectification and many social influences, including the mass media, parents, and peers reinforce self-objectification (Fredrickson & Roberts, 1997; Rousseau & Eggermont, 2018; Webb et al, 2017). Development of effective prevention programs requires research to identify which sources of sexual objectification are more likely to result in self-objectification among children and to identify other potential antecedents of self-objectification.…”
Section: Discussionmentioning
confidence: 99%
“…), ou seja, a pesquisa ocorre em um único momento, de forma observacional e com uma população específica para o estudo. O desenho de pesquisa longitudinal, por sua vez, foi menos empregado (ESPINOZA;PENELO;RAICH, 2013;GOLAN;HAGAY;TAMIR, 2014;GORDON et al, 2021;REGEHR et al, 2020;ROUSSEAU;EGGERMONT, 2018;SUNDGOT-BORGEN et al, 2019;WADE et al, 2017) e consiste em acompanhar a população do estudo ao longo do tempo, observando as possíveis mudanças que ocorrem (HOCHMAN et al, 2005).…”
Section: Figura 2 -Cronologia Das Publicaçõesunclassified
“…With respect to norm emergence and awareness , there is ample evidence that peers and media are powerful agents in transmitting and promoting norms of attractiveness among adolescents (e.g. Rousseau and Eggermont, 2018; Webb et al, 2017). Both sociocultural agents have been found to promote thinness and muscularity as central aspects of attractiveness, shaping, and reinforcing the thin/athletic-ideal (Rodgers et al, 2019).…”
Section: Adolescents’ Thin/athletic-ideal Internalizationmentioning
confidence: 99%